Performance - Webber, Joel (Addison-Wesley, 2007)
"A Google mantra: 'Fast is better than slow.' GWT's emphasis on end-user experience makes performance a critical requirement. When used appropriately, the GWT architecture can help you deliver sophisticated web apps that have unmatched startup speed and performance. However, it's easy to misuse GWT: Choosing a suboptimal architecture or writing unnecessarily generalized code can make your application run like a dog (a slow dog, that is). Join the co-creator of GWT as he demonstrates best practices for web application performance and explains how to implement them using GWT."--Resource description page